The Effectiveness of Mindfulness-Based Cognitive Therapy on Anxiety and Rumination in Women with Body Dysmorphic Disorder - Haghdoost, Fatemeh; Giti Ghoreishi, Ashrafalsadat (Mental Health and Lifestyle Journal, 2024)
The present study aimed to examine the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) on anxiety and rumination levels in women diagnosed with Body Dysmorphic Disorder (BDD). This study employed a quasi-experimental design with pre-test and post-test measures to assess changes in both the experimental and control groups. The statistical population consisted of all women diagnosed with BDD who attended counseling centers in Tehran in 2024. A sample of 30 women with this disorder was voluntarily and non-randomly selected from the counseling centers in Tehran and then randomly assigned to two groups: an experimental group (n = 15) and a control group (n = 15). The instruments used in this study were the Beck Anxiety Inventory and the Ruminative Response Scale developed by Nolen-Hoeksema and Morrow. For data analysis, multivariate analysis of covariance (MANCOVA) was employed. The results revealed a significant difference between the experimental and control groups at the post-test stage in the variables of anxiety and rumination. It can be concluded that Mindfulness-Based Cognitive Therapy is effective in reducing anxiety and rumination in women with Body Dysmorphic Disorder.